1998
DOI: 10.5194/hess-2-303-1998
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impacts of major anion variations on surface water acidity particularly with regard to conifer harvesting: case studies from Wales and Northern England

Abstract: Abstract. Data on the water quality of streams draining a range of acidic and acid sensitive, mainly afforested, upland catchments in mid- and north-Wales and northern-England are described to investigate the acidification effects of conifer harvesting in relation to natural variability. Most sites show a large range in pH and major cation and major anion concentrations. The waters draining from the smaller catchments are more acidic and aluminium bearing reflecting a higher proportion of runoff from the acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…l Increases in potassium and bromine with felling are associated with the breakdown of organic matter with insufficient biological uptake; similar behaviour has been observed within the Plynlimon area (Neal et al, 1992a,b). l A gradual reduction in sodium and chloride for the response site during and post-felling has been observed for other small streams in the Plynlimon area (Neal et al, 1998a). The concentrations of sodium and chloride have reduced by about a third from the time of fell to the end of the monitoring period four years later.…”
Section: Water Quality Results For the Paired Streamsmentioning
confidence: 87%
See 1 more Smart Citation
“…l Increases in potassium and bromine with felling are associated with the breakdown of organic matter with insufficient biological uptake; similar behaviour has been observed within the Plynlimon area (Neal et al, 1992a,b). l A gradual reduction in sodium and chloride for the response site during and post-felling has been observed for other small streams in the Plynlimon area (Neal et al, 1998a). The concentrations of sodium and chloride have reduced by about a third from the time of fell to the end of the monitoring period four years later.…”
Section: Water Quality Results For the Paired Streamsmentioning
confidence: 87%
“…However, the changes are matched by similar changes in the control. In an earlier study, Neal et al (1998a) showed that, at the response site, there was some acidification associated with felling as post-felling the waters were of lower Gran alkalinity for a given flow, while for the control there was no such separation. Undertaking a similar analysis of Gran alkalinity, Neal et al (1998) revealed the same pattern for the full dataset, but there may be a small reduction in acidity late on during the recovery stage of felling.…”
Section: Water Quality Results For the Paired Streamsmentioning
confidence: 99%
“…For the gley catchments, phosphate can be released to the soil water and, thence, to the stream. However, in the phosphorus-limiting conditions prevalent in most of the uplands, the release of phosphate is taken up rapidly by the biota and this may even lead to the loss of the nitrate signal in the stream that would naturally be expected following felling (Neal et al, 1998a(Neal et al, ,b, 2004c. All of this is extremely good news for present day UK forestry management practices except for the fact that Fe seems to be increasing in concentration in the Plynlimon forested catchments (Neal et al, 2004d,e).…”
Section: Water Qualitymentioning
confidence: 99%
“…Malcolm et al (2004) clearly indicate variability in temperature and light regime for shaded and unshaded streams in moorland and forested terrains in the Cairngorms and this, in part, will influence biology. This variability changes according to local conditions and there is much heterogeneity, even for critical components such as acid neutralisation capacity, with heterogeneity increasing at finer and finer scales (Neal et al, 1997b(Neal et al, , 1998aReynolds et al, 2001).…”
Section: Biologymentioning
confidence: 99%
“…However, the beneficial effects of whole-tree harvesting in reducing leaching losses of both nitrogen and base cations can be more than outweighed by the longerterm acidification because of the greater removal of base cations in harvested products (Reynolds and Stevens, 1998). More nitrate leaching is generally observed in minicatchments draining relatively aerobic soils such as podzols compared to anaerobic gley soils (Neal et al, 1998b (Stevens et al, 2001).…”
Section: Short-term Acidification Impact Of Clearfellingmentioning
confidence: 99%